43. CLINICAL, PARACLINICAL SYMPTOMS, AND TREATMENT IN 12 PATIENTS WITH TUBERCOLOUS CONSTRICTIVE PERICARDITIS IN THE DEPARTMENT OF GENERAL INTERNAL MEDICINE AT THE NATIONAL LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Review the clinical and paraclinical characteristics, diagnosis and treatment results of patients with tubercular constrictive pericarditis.Subjects and methods: Study on a cluster of cases, a retrospective descriptive study at the General Internal Medicine Department of the National Lung Hospital, from January 2023 to December 2023, we admitted and treated 12 patients.Results: Tuberculous constrictive pericarditis was found in 13.8% of patients with tuberculous pericarditis. The average age of patients was 53.0 ± 18.0. Symptoms included dyspnea 100%, edema 75%, cough 100%, and fever 41.7%. All patients (100%) showed symptoms of right heart failure, with NYHA classification: NYHA II 33.3%, NYHA III 41.7%, NYHA IV 25%. Chest X-ray detected tuberculosis in 75%, and chest CT scan in 83.3%. Bilateral pleural effusion was found in 91.7%, and ascites in 66.7%. The pleural effusion was mainly exudative with ADA 41.8 ± 11.4 u/l. Evidence-based diagnosis of tuberculosis was confirmed in 33.3%. Surgery was performed in 25% of patients. The rate of patients with treatment failure is 25%.Conclusion: Tuberculous Constrictive Pericarditis often progresses insidiously and is a characteristic of tuberculous pericarditis. Diagnosis remains challenging. However, initial diagnosis can be made through imaging and other characteristic signs such as clinical examination, risk factors, and identifying tuberculosis lesions in other organs. Early pericardiectomy should be performed, followed by continued anti-tuberculosis regimen and corticosteroids. The mortality rate remains high.
Keywords: Tuberculosis, tuberculous pericarditis, constrictive pericarditis.